In vitro Effectiveness of 2-Propanol Based Hand and Skin Disinfectants Against Various Microorganisms - Ozkalp, Birol; Musa Ozcan, Mehmet; Kocak, Raziye; Ozcan, Mustafa (Asian Journal of Chemistry, 2011)
In this study, in order to define how effective alcohol based hand and skin disinfectant against Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 23853), Candida albicans (ATCC 10231) strains are reported. To test the final microorganisms at different concentrations of the disinfectant to be tested by being prepared as 2-5 × 109 CFU/mL according to the McFarland 5 cloudiness of test disinfectant. After disinfectants were activated with microorganisms at previously experimented 30 s, 1, 5, 15 and 30 min periods, colony counts at 1 mL. Levels were performed by way of cast-cultural plaque method. Consequently, it was determined that 100 % concentration of alcohol based skin and hand disinfectant was effective against Staphylococcus aureus in 1 min, while other test microorganisms were effective in 30 s.